Cartilage-specific ablation of XBP1 signaling in mouse results in a chondrodysplasia characterized by reduced chondrocyte proliferation and delayed cartilage maturation and mineralization. Issue 4 (April 2015) - Cameron, T.L.; Gresshoff, I.L.; Bell, K.M.; Piróg, K.A.; Sampurno, L.; Hartley, C.L.; Sanford, E.M.; Wilson, R.; Ermann, J.; Boot-Handford, R.P.; Glimcher, L.H.; Briggs, M.D.; et al.
Summary: Objective: To investigate the in vivo role of the IRE1/XBP1 unfolded protein response (UPR) signaling pathway in cartilage. Design: Xbp1 flox/flox . Col2a1 - Cre mice ( Xbp1 CartΔEx2 ), in which XBP1 activity is ablated specifically from cartilage, were analyzed histomorphometrically by Alizarin red/Alcian blue skeletal preparations and X-rays to examine overall bone growth, histological stains to measure growth plate zone length, chondrocyte organization, and mineralization, and immunofluorescence for collagen II, collagen X, and IHH. Bromodeoxyuridine (BrdU) and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) analyses were used to measure chondrocyte proliferation and cell death, respectively. Chondrocyte cultures and microdissected growth plate zones were analyzed for expression profiling of chondrocyte proliferation or endoplasmic reticulum (ER) stress markers by Quantitative PCR (qPCR), and of Xbp1 mRNA splicing by RT-PCR to monitor IRE1 activation. Results: Xbp1 CartΔEx2 displayed a chondrodysplasia involving dysregulated chondrocyte proliferation, growth plate hypertrophic zone shortening, and IRE1 hyperactivation in chondrocytes. Deposition of collagens II and X in the Xbp1 CartΔEx2 growth plate cartilage indicated that XBP1 is not required for matrix protein deposition or chondrocyte hypertrophy. Analyses of mid-gestation long bones revealed delayed ossification in Xbp1 CartΔEx2 embryos. The rate of chondrocyte cell death was not significantly altered, and only minimal alterations in the expression of key markers of chondrocyte proliferation were observed in the Xbp1 CartΔEx2 growth plate. IRE1 hyperactivation occurred in Xbp1 CartΔEx2 chondrocytes but was not sufficient to induce regulated IRE1-dependent decay (RIDD) or a classical UPR. Conclusion: Our work suggests roles for XBP1 in regulating chondrocyte proliferation and the timing of mineralization during endochondral ossification, findings which have implications for both skeletal development and disease.